2015
DOI: 10.1371/journal.pone.0145790
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone Enhances the Radiosensitivity of UMSCC-10A Cells via Specific Inhibition of Erk1/2 Phosphorylation

Abstract: BackgroundAlthough radiotherapy is one of the mainstream approaches for the treatment of head and neck squamous cell carcinoma (HNSCC), this cancer is always associated with resistance to radiation. In this study, the mechanism of action of isoalantolactone as well as its radiosensitizing effect was investigated in UMSCC-10A cells.MethodsThe radiosensitization of UMSCC-10A cells treated with isoalantolactone was analyzed by colony formation assay. The radiosensitization effects of isoalantolactone on cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, the inhibitory effect of IAL on the phosphorylation of JNK and p38 MAPK was not significant. It was reported that IAL could overcome resistance to radiation in UMSCC-10A cells by specifically inhibiting the activation of the Erk1/2 signaling pathway [39]. The MAPKs are activated by phosphorylation caused by specific MAP kinase kinases (MKKs), which, in turn, are activated by MKK kinases [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibitory effect of IAL on the phosphorylation of JNK and p38 MAPK was not significant. It was reported that IAL could overcome resistance to radiation in UMSCC-10A cells by specifically inhibiting the activation of the Erk1/2 signaling pathway [39]. The MAPKs are activated by phosphorylation caused by specific MAP kinase kinases (MKKs), which, in turn, are activated by MKK kinases [40].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that IATL can induce a highly selective cytotoxic effect, while its toxicity to the body's normal peripheral blood lymphocytes is very low . The antitumor properties of IATL in lung and breast cancers have already been reported . However, the effects of IATL in GBM have not yet been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…One of our main discovery was that FTO protein levels in the pancreas were associated with energy intake: low on low energy diet and high on high energy diet, compared to normal diet. Earlier in vitro studies showed that FTO overexpression in MIN6 (mouse insulinoma) cells significantly inhibited insulin secretion in the presence of glucose, but did not affect insulin expression 47 . As a result, we argue that increased FTO levels in the pancreas may directly influence insulin release from beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of Fto mRNA and protein levels was previously studied by several research groups, primarily using rodent models 26 , 29 , 31 , 42 , 47 49 . The role of Fto in rodents is, however, limited as compared to humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation